MAKNA DENOTATIF DAN KONOTATIF DALAM PUISI RAʾAYTU ʿALĀ LAWḤI AL-KHAYĀLI YATĪMAH KARYA AHMAD SYAUQI: PENDEKATAN SEMANTIK معاني الظاهرة و الضمنية في قصيدة ”رأيت على لوح الخيالي ياتيمة“ لأحمد شوقي: الدراسة الدلاليّة - Aeni Lukviati Urbah; Yayan Rahtikawati; Maman Abdul Djaliel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the diction that undergoes a transformation from denotative to connotative meaning and to describe the process of meaning formation in the poem Raaytu ala Lawhi al-Khayali Yatimah by Ahmad Shawqi. The study is motivated by the nature of poetic language, which conveys meaning not only through lexical references but also through poetic context, association, symbolism, and cultural experience, thereby generating complex connotative meanings. This research employed a qualitative approach with a descriptive method. The data consisted of lexical items containing denotative and connotative meanings found in the poem Raaytu ala Lawhi al-Khayali Yatimah. Data were collected through reading and note-taking techniques and analyzed using the translational equivalent method and the distributional method employing Immediate Constituent Analysis, substitution, and expansion techniques. The analysis was grounded in Geoffrey Leech's semantic theory, particularly his classification of denotative and connotative meanings, and was further supported by the Arabic semantic concepts of dalalah lafziyyah (lexical meaning) and dalalah ihaiyyah (connotative meaning) to explain the relationship between lexical and contextual meanings. The findings reveal 14 lexical items that undergo a shift from denotative to connotative meaning. The meaning formation includes transformations from concrete to abstract concepts, objects into symbols, sensory experiences into emotional experiences, body parts into symbols of protection or destruction, and physical actions into representations of humanitarian values. Four lexical items produce positive connotations, whereas ten generate negative connotations. The predominance of negative connotations demonstrates that Ahmad Shawqi employs diction not merely as an aesthetic element but also as a humanitarian medium to portray the suffering of orphans caused by war and to evoke readers' empathy toward social tragedy.